Development and comparison of an esophageal Doppler monitoring-based treatment algorithm with a heart rate and blood pressure-based treatment algorithm for goal-directed fluid therapy in anesthetized dogs: A pilot study - Henze, Inken Sabine; Hilpert, Laura; Kutter, Annette P. N. (Frontiers in Veterinary Science, 2022)
The objective of this pilot study was to determine the feasibility of a study comparing the efficacy of an esophageal Doppler monitor (EDM)-based fluid therapy algorithm with a heart rate (HR)- and mean arterial blood pressure (MAP)-based algorithm in reducing hypotension and fluid load in anesthetized dogs. Client-owned dogs undergoing general anesthesia for surgical procedures were randomized to two groups. An EDM probe for monitoring blood flow in the descending aorta was placed in each dog before receiving a crystalloid bolus (5 mL/kg) over 5 minutes. Fluids were repeated in case of fluid responsiveness defined by increasing Velocity Time Integral (VTI) ≥ 10% in group EDM and by decreasing HR ≥ 5 beats/minute and/or increasing MAP ≥ 3 mmHg in group standard. The feasibility outcomes included the proportion of dogs completing the study and the clinical applicability of the algorithms. The clinical outcomes were the total administered fluid volume and the duration of hypotension defined as MAP < 60 mmHg. Data was compared between groups with Mann-Whitney U test. p-values < 0.05 were deemed significant. Of 25 dogs screened, 14 completed the study (56%). There were no differences in the proportion of recorded time spent in hypotension in group standard (2 (0 – 39) % (median(range))) and EDM (0 (0 – 63) %, p = 1), or the total volume of fluids (standard 8 (5 –14) mL/kg/h, EDM 11 (4 – 20) mL/kg/h, p = 0.3). This study declined the feasibility of a study comparing the impact of two newly developed fluid therapy algorithms on hypotension and fluid load in their current form. Clinical outcome analyses were underpowered and no differences in treatment efficacy between the groups could be determined. The conclusions drawn from this pilot study provide important information for future study designs.